Chemical Constituents of Calophyllum Inophyllum and Cratoxylum Glaucum (Guttiferae) - Kua, Audrey Siew May (2006)
Extensive studies on the plants, Calophyllum inophyllum and Cratoxylum glaucum have resulted in the isolation of ten compounds. All these compounds were isolated by means of chromatographic methods and their structures derived on the basis of spectroscopic evidence, mainly 1D and 2D nuclear magnetic resonance spectroscopy. Chemical investigations on the root bark extracts of Calophyllum inophyllum has yielded two new xanthones, inophyllin A and inophyllin B, three known xanthones, brasilixanthone B, tovopyrifolin C, caloxanthone B, one triterpene, friedelin and one triterpenoid, -sitosterol. Cratoxylum glaucum afforded two triterpenes, friedelin and stigmasterol, two known anthraquinones, 1,8-dihydroxy-3-methoxy-6-methylanthraquinone and vismiaquinone and a known xanthone, dimethylmangostin. Cytotoxic assay was performed using CEM-SS Cell Line. All the crude extracts of Calophyllum inophyllum and Cratoxylum glaucum showed no activity. Antimicrobial assay was carried out towards four pathogenic bacteria, Methicillin Resistant Staphylococcus aures, Pseudomonas aeruginosa, Staphylococcus typhimurium and Bacillus subtilis. Most of the crude extracts tested against these microbes gave no activity. Larvicidal test was carried out towards the larvae of Aedes aegypti. The larvae were not susceptible to all of the crude extracts and pure compounds of Calophyllum inophyllum and Cratoxylum glaucum